STRATEGI BRANDING DAN KONSEP PUBLIKASI BERBASIS LOCAL TOURISM DI ERA 4.0 (Studi kasus media sosial dan peran Desain Komunikasi visual) - Darmawanto, Eko; Wijanarko, Kukuh Dwi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
Branding is introducing an image of both services and physical products, the process taken must have a strategy and preparation of measurable time targets. There are many ways to introduce a product, which is the current trend of the 4.0 era where most transactions and information are traded in the IoT-based world. Local tourism has now developed, by utilizing the potential of the surrounding nature and then being developed as the basis for the products offered, improvements are made in various sectors to support the display to boost publications, of course with a communication angle. The need for researchers to take steps to dissect the flow in building a publication concept in the form of a realistic road map with applied strategies and analysis combined with good publication management is the core of the research carried out. The design thinking method is applied to dissect what strategic steps will be used in determining the core of the publication with impact factors. Local tourism branding and publication strategies are influenced by engagement from the psychological model of one touch flayer of social media users related to the happynest side factor that affects the pattern of attractive content with a high response rate and saddnes side factor which is empathetic with a low response rate.